ORTAÇAĞDA İLK ÜNİVERSİTELER : STUDIUM GENERALE - Fatih Rukancı; Hakan Anameriç (Felsefe Dünyası)
This paper, basically, examines medieval universities as the most important foundations in the Middle Ages into the approach of their being founded, and evolvement, and education and training methodologies under the political and intellectual conditions of that time. Moreover, various concepts regarding medieval universities are explained. The universities of the middle ages, constituted as a form of conventional society at the beginning, are also elucidated by means of their roles and contributions to exploring new scientific branches. On the otherer hand, it is observed that being privaleged as the faculty and scholars of the universities under a remarkable scholastic and administrative pressure is also considerable for the future mission of these institutions. It is also given attention of these first universities in Europe, formerly known as Studium Generale has certain differences with their education programs and curriculum as well as their campus life